Problems of implementation of the intellectual property rights on information resources in Ukraine - Татарникова, Кристина Геннадіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
This article describes the problems of implementation of the intellectual property rights on information resources in Ukraine. The author analyzed the mechanism of implementation of this right, concluded that this area contains a number of problems in Ukraine which demand being solved with the goal of full realization of this right by citizens, organizations, commercial firms. Specific legal measures aimed at improving the process of implementation of intellectual property rights on information resources in Ukraine are justified in the work, the author also gives the proposals how to simplify the procedures of obtaining domain names and registering in the Ukrainian legislation provisions that will provide web sites the signs of independent intellectual property.